Pharmaceutical Analytics: Methods of Analysis of Medicinal Products and their Quality Control - Borysiuk, Iryna; Dvulit, Iryna; Katruk, Leonid (International Journal of Statistics in Medical Research, 2024)
The importance of evaluating the quality of medicinal products is determined by their impact on public health, therefore there are many analytical methods for controlling the chemical composition and bioequivalence of medicines. Falsification of medicines and determining the composition of generics also remain a serious problem, therefore the search and systematization of modern methods of identifying the quality of medicines and methods of combating illegal medicines are relevant and timely. The purpose of the study is to determine effective methods of assessing the quality of medicines and methods of combating falsified medicines, which would meet the country’s demands in conditions of war and economic crisis. The research used methods of analysis, synthesis, systematization, statistical comparison of groups using Student’s t-test, survey and generalization of results. The obtained results revealed alternative methods of quality control of medicinal products in the conditions of economic and war crisis. We identified the prospect of introducing drug marking and assisting pharmaceutical manufacturers and distributors in drug marking. A low level of awareness of the population regarding the methods of assessing the quality of medicinal products and the algorithm of actions in case of detection of low-quality medicinal products was revealed. Among the doctors, there was also an insufficient level of knowledge regarding the assessment of the quality of medicines, which requires the introduction of training of doctors in this field and educational work among the population.